Maternal age effects on myometrial expression of contractile proteins, uterine gene expression, and contractile activity during labor in the rat - Elmes, Matthew; Szyszka, Alexandra; Pauliat, Caroline; Clifford, Bethan; Daniel, Zoe; Cheng, Zhangrui; Wathes, Claire; McMullen, Sarah (Wiley Open Access, 2015)
Advanced maternal age of first time pregnant mothers is associated with prolonged and dysfunctional labor and significant risk of emergency cesarean section. We investigated the influence of maternal age on myometrial contractility, expression of contractile associated proteins (CAPs), and global gene expression in the parturient uterus. Female Wistar rats either 8 (YOUNG n = 10) or 24 (OLDER n = 10) weeks old were fed laboratory chow, mated, and killed during parturition. Myometrial strips were dissected to determine contractile activity, cholesterol (CHOL) and triglycerides (TAG) content, protein expression of connexin-43 (GJA1), prostaglandin endoperoxide synthase 2 (PTGS2), and caveolin 1 (CAV-1). Maternal plasma concentrations of prostaglandins PGE2, PGF2a, and progesterone were determined by RIA. Global gene expression in uterine samples was compared using Affymetrix Genechip Gene 2.0 ST arrays and Ingenuity Pathway analysis (IPA). Spontaneous contractility in myometrium exhibited by YOUNG rats was threefold greater than OLDER animals (P < 0.027) but maternal age had no significant effect on myometrial CAP expression, lipid profiles, or pregnancy related hormones. OLDER myometrium increased contractile activity in response to PGF2a, phenylephrine, and carbachol, a response absent in YOUNG rats (all P < 0.002). Microarray analysis identified that maternal age affected expression of genes related to immune and inflammatory responses, lipid transport and metabolism, steroid metabolism, tissue remodeling, and smooth muscle contraction. In conclusion YOUNG laboring rat myometrium seems primed to contract maximally, whereas activity is blunted in OLDER animals and requires stimulation to meet contractile potential. Further work investigating maternal age effects on myometrial function is required with focus on lipidmetabolism and inflammatory pathways.